2012
DOI: 10.1016/j.envres.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and mercury molar ratios in saltwater fish from New Jersey: Individual and species variability complicate use in human health fish consumption advisories

Abstract: Balancing risk versus benefits to humans and other organisms from consuming fish is a national concern in the USA, as well as in many other parts of the world. Protecting public health is both a federal and state responsibility, and states respond by issuing fish consumption advisories, particularly for mercury. Recently it has been emphasized that the protective role of selenium against mercury toxicity depends on their molar ratios, which should be evaluated as an indication of selenium’s protective capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 86 publications
7
42
1
1
Order By: Relevance
“…Several authors have argued that higher Se:Hg molar ratios indicate a more protective effect of selenium against mercury toxicity (Ralston 2008;Peterson et al 2009a, b), even though contradictory results indicate that the effect of selenium on mercury bioaccumulation is an extremely complex process (Dang and Wang 2011). There has been a growing concern about the evaluation of Se:Hg molar ratios in fish muscle with focus on the methylmercury toxicity for humans as consumers of fish (Kaneko and Ralston 2007;Ralston 2008Ralston , 2009Ralston et al 2008;Burger and Gochfeld 2012). In the present study, the muscular Se:Hg molar ratio in S. salpa from Mahdia was significantly higher than in S. salpa from Sfax.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have argued that higher Se:Hg molar ratios indicate a more protective effect of selenium against mercury toxicity (Ralston 2008;Peterson et al 2009a, b), even though contradictory results indicate that the effect of selenium on mercury bioaccumulation is an extremely complex process (Dang and Wang 2011). There has been a growing concern about the evaluation of Se:Hg molar ratios in fish muscle with focus on the methylmercury toxicity for humans as consumers of fish (Kaneko and Ralston 2007;Ralston 2008Ralston , 2009Ralston et al 2008;Burger and Gochfeld 2012). In the present study, the muscular Se:Hg molar ratio in S. salpa from Mahdia was significantly higher than in S. salpa from Sfax.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, selenium is though to have a protective effect against mercury toxicity (Kaneko and Ralston 2007;Ralston 2008Ralston , 2009Ralston et al 2008;Burger and Gochfeld 2012) mainly because of the high affinity of selenium to mercury. In fact, selenium is thought to sequester methylmercury and reduce its bioavailability in organisms (Sørmo et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Ralston et al (2008) showed that Se:Hg molar ratios above 1 protect against Hg toxicity. However this ratio definitively depends o species-specific toxic-kinetics processes (Watanabe, 2002;Burger and Gochfeld, 2012). This feature leads to a wide variability of Se:Hg molar ratios and makes difficult their use in risk assessment.…”
Section: Sources Of Hgt and Fish Contamination In Augusta Baymentioning
confidence: 99%
“…Fish provide an important source of protein and omega-3 (n − 3) polyunsaturated fatty acids (PUFAs) for human (Albert et al, 2002;Burger & Gochfeld, 2012). However, deterioration of fish flesh quality leads to poor consumer acceptance, increases the risk of cardiovascular disease in humans and causes huge economic losses for producers (Hosseini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%